2022
DOI: 10.1155/2022/2904910
|View full text |Cite|
|
Sign up to set email alerts
|

Assessment of Awareness and Practice toward Diabetic Ketoacidosis among Diabetic Patients and Their Caregivers in Hail Region

Abstract: Introduction. Diabetic ketoacidosis (DKA) is one of the most serious consequences of diabetes. This serious issue occurs when the body cannot use the glucose as a source of energy because of a lack in the level of insulin which as consequence will lead to an increased level of glucose resulting in DKA. Aim. The goal of this study was to increase diabetic patients’ and caregivers’ awareness and practice of DKA at the community level in Hail City, Saudi Arabia, in 2022. The assessment of people’s awareness and k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…DKA diagnosis and having adequate information about DKA did (P 0.05) (Alreshidi et al, 2022). In contrast, results from another study showed that characteristics that were significantly associated with lower parents' knowledge included being a father, aged >40 years, less than university educated, unemployed or those whose occupation was not healthcare-related (Alhomood et al, 2020).…”
Section: Discussionmentioning
confidence: 89%
See 4 more Smart Citations
“…DKA diagnosis and having adequate information about DKA did (P 0.05) (Alreshidi et al, 2022). In contrast, results from another study showed that characteristics that were significantly associated with lower parents' knowledge included being a father, aged >40 years, less than university educated, unemployed or those whose occupation was not healthcare-related (Alhomood et al, 2020).…”
Section: Discussionmentioning
confidence: 89%
“…This was higher than reported in a cross-sectional online survey was conducted among 348 people from Hail City, Saudi Arabia, found that 43.7% of the respondents were correct that DKA is an emergency complication of DM that required urgent intervention. Only 17.8% of the respondents were aware that DKA is not only for children and more than half (51.1%) believed that maintaining the normal level of A1c reduces the incidence of DKA (Alreshidi et al, 2022). Generally, the results show that more than two-thirds (67.8%) of the subjects were assumed to have poor awareness levels, 23.6% were moderate and only 8.6% were good (Alreshidi et al, 2022).…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations